SEJARAH DAN PELESTARIAN KESENIAN MUSIK CALEMPONG BAOGUONG DI KOTA BANGKINANG KABUPATEN KAMPAR - Beni Bopindo; Prof. Dr. Isjoni, M.Si '; Marwoto Saiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: art is the result of human action arising out of life and have aestethic value. Art consists of various type that include traditional music art. One of which is the art of traditional music Calempong Baoguong in Bangkinang City Kampar District. This research have a purpose to know about (1) history of musical art Calempong Baoguong in Bangkinang City Kampar District. (2) role of the government in preservation of musical arts Calempong Baoguong in Bangkinang City Kampar District. (3) role of the education department in preservation of musical arts Calempong Baoguong in Bangkinang City Kampar District. (4) role of the people in preservation of musical art Calempong Baoguong in Bangkinang City Kampar District. (5) the benefit from preservation of musical arts Calempong Baoguong in Bangkinang City Kampar District. This research use a qualitative method with approach history and collect document with observation, interview and document or library studies. Interviewers in this research is culture chair of Kampar District, people in education department of Bangkinang City Kampar District. Result of the research is show that of musical arts Calempong Baoguong begin spreading from West Sumatera up to Kampar District. The spreading process through migration people from West Sumatera to Kampar District and in a way of dominate place by Pagaruyung Kingdom at 14 Century when Adityawarman leadership. Now the musical of arts Calempong Baoguong preserved by government, education departemet and people in Bangkinang City Kampar District in every event.Key words: Calempong Baoguong, art of Kampar.